Changes in the agriculture specialization Cherkasy region over 10 years - I. O. Zozulia (Людина і довкілля: Проблеми неоекології)
Production typology of agriculture is the most recent direction of geographical research in agriculture, which has its roots in the 19th century. However, the decline in its popularity in recent decades is associated with an extremely complex and labor-intensive method that involves the processing of large data sets. Assessments of the ecological impact on landscapes of certain combinations of industries are extremely relevant. Assessments of environmental services provided by agro-ecosystems are also relevant today.